Temperature-dependent X-ray Studies Of Discotic Hexagonal Columnar Mesophases In Trinuclear Gold(I) Pyrazolate Complex - Mohamad Azani Abd Khadir Jalani; Hendrik O. Lintang; Siew Ling Leeb; Juan Matmin; Nur Fatiha Ghazalli; Leny Yuliati; Amy Zuria Abdul Ajid; Mohd Izam Idrus (Penerbit UTM Press, 2024)
Indexed by WOS/MyCite